Analysis of the effect of BMI on depression and anxiety among older adults in China: the mediating role of ADL and IADL - Qiao, Ziqing; Wang, Zichun; Qiu, Jiaping; Zhang, Jie; Cao, Weiyi (Frontiers in Public Health, 2024)
Background Anxiety and depression are serious psychological and public health issues among the older adults. Currently, there is a lack of understanding of the relationship between Body Mass Index (BMI) and anxiety or depression symptoms in the older adult population in China. Therefore, the purpose of this study is to investigate the impact of BMI on anxiety and depression through correlation analysis in different subgroups and to examine the potential chain mediating effects of Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) between BMI and symptoms of anxiety and depression. Methods From the CLHLS database conducted in 2017–2018, data regarding height, weight, anxiety symptoms, depression symptoms, as well as demographic, socioeconomic, behavioral, and health-related characteristics were collected. Multivariate logistic regression analysis was used to explore the impact of BMI on anxiety and depression symptoms. Finally, the SPSS macro process was utilized to test the multiple mediating effects of ADL and IADL between BMI and anxiety or depression symptoms. Results After screening, a final sample of 9,098 Chinese older adult individuals aged 65 and above was selected. Among them, 1,074 cases (11.8%) exhibited anxiety symptoms, 1,458 cases (16.0%) exhibited depressive symptoms. Compared to normal BMI, the adjusted analysis showed that underweight in Chinese older adult individuals was significantly associated with anxiety (OR = 1.316, p = 0.004) and depression (OR = 1.232, p = 0.013). This relationship was found to be more significant in males, individuals aged 80 and above, unmarried individuals, and those residing in town. ADL and IADL played a chain-mediated role between BMI and anxiety symptoms in the older adult. BMI not only had a direct effect on anxiety symptoms in the older adult (effect = −0.0159; SE = 0.0066; 95%CI: LL = −0.0288, UL = −0.0031), but also influenced them indirectly through two pathways: the independent mediating role of IADL (effect = −0.0010; SE = 0.0005; 95%CI: LL = −0.0018, UL = −0.0003) and the chain-mediated role of ADL and IADL (effect = −0.0012; SE = 0.0004; 95%CI: LL = −0.0020, UL = −0.0006). Conclusion In the older adult individuals in China, underweight is associated with an increased risk of anxiety and depression symptoms. Improving the underweight condition of Chinese older adult individuals can reduce their ADL and IADL limitations, thereby benefiting their mental health.